Adab kepada Guru dan Orang Tua: Studi Pemahaman Siswa pada Materi Akhlak - Sari, Leni Elpita; Rahman, Abdul; Baryanto, Baryanto (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
A good moral character is a keyword for the success of educational processes. Everyone will never be able to control themselves if only relying on the knowledge they have without being espoused by a noble moral character. Hence, each teacher who establishes interactions with students is given a big responsibility to guide his/her students’ moral character. Seeing that responsibility, the current study aimed at finding out the depiction of the teacher’s efforts to give understanding to students in a public school, MTS No. 2 Kepahiang, as regards good manners to parents and teachers, using a qualitative approach with the primary informant, namely the Akidah Akhlak teacher in that school. This study concluded that the teacher handling Akidah Akhlak lesson had made good efforts and been adequately helpful in giving understanding to students about good manners to parents and teachers. This entity was seen from students’ behavior in doing their activities both at school and afterschool although based on the evaluation results, it was not a hundred percent of students who had been able to apply their understanding of the importance of good manners to parents and teachers. Akhlak yang baik adalah kata kunci keberhasilan proses pendidikan. Setiap orang tidak akan mampu mengendalikan dirinya jika hanya bersandar pada pengetahuan yang dimilikinya kecuali dibarengi dengan akhlak mulia. Dengan demikian setiap guru yang melakukan interaksi dengan murid diberikan tanggungjawab yang besar untuk membina akhlak anak didiknya. Melihat besarnya tanggungjawab itu penelitian ini bertujuan untuk menemukan gambaran tentang upaya guru dalam memberikan pemahaman kepada siswa di MTs. Negeri 02 Kepahiang tentang adab baik kepada orang tua maupun guru, melalui pendekatan kualitatif dengan informan utama yaitu guru Akidah Akhlak di sekolah tersebut. Peneltian ini memperoleh simpulan bahwa guru pelajaran akidah akhlak sudah berusaha dan cukup membantu dalam memberikan pemahaman kepada siswa dalam hal adab kepada orang tua dan guru, hal ini terlihat dari perilaku peserta didik dalam menjalani aktivitas di sekolah maupun di luar sekolah meskipun dari hasil evaluasi belum sepenuhnya siswa mampu menerapkan pemahaman mereka tentang pentingnya adab baik kepada orang tua maupun guru.